The Curriculum Evaluation on Bachelor of Education in Biology Major at Rajabhat Maha Sarakham University, Thailand - Sarnkong, Rattikan; Akakul, Paisan (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purpose of this research to evaluate the curriculum of the Bachelor of Education Program in biology of 34Rajabhat Maha Sarakham University 2006 revised in 2008 focusing on curriculum contents and products. The 245 samples were university students, graduates and assistant teachers. They were selected by the stratified random sampling method. The instrument was a questionnaire. The statistics used were percentage, mean and standard deviation. The research revealed that 1) The overall opinion of the research findings showed that the overall opinion of the university students on the curriculum contents was at a high level, 2) Regarding the assessment of primary factors, the overall opinion of the university students and graduates on the primary factors was at a high level, 3) Regarding the evaluation of curriculum process, the overall opinion of the university students and graduates on the curriculum process was at a high level and 4) The overall opinion of the assistant teachers toward the required intern students was at a high level.